2023
DOI: 10.3390/microorganisms11010122
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Analysis on the Occurrence of Salmonella enterica Subspecies enterica Serovar Dublin in the German Federal State Schleswig-Holstein Using Whole-Genome Sequencing

Abstract: The cattle-adapted serovar Salmonella Dublin (S. Dublin) causes enteritis and systemic diseases in animals. In the German federal state Schleswig-Holstein, S. Dublin is the most important serovar in cattle indicating an endemic character of the infection. To gain information on dissemination and routes of infection, whole-genome sequencing (WGS) was used to explore the genetic traits of 78 S. Dublin strains collected over a period of six years. The phylogeny was analysed using core-genome single nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, cow pats may act as a reservoir for Salmonella transmission between grassing seasons [ 76 ]. Pasture areas used by other foreign cows, application of manure from infected herds close to or directly on pastures without an adequate resting period is, therefore, thought to be an important S. Dublin transmission route and an efficient pathway for the establishment of the bacteria within a herd [ 35 ]. The probability of establishment was highlighted by Fossler et al, who identified a significant risk of shedding of Salmonella bacteria in cows in dairy herds with previous Salmonella history if their own manure was applied to owned or rented land or if cows ate roughage or grassed fields where manure had been applied to the ground surface without additional ploughing [ 78 ].…”
Section: Resulting Biosecurity Assessment Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cow pats may act as a reservoir for Salmonella transmission between grassing seasons [ 76 ]. Pasture areas used by other foreign cows, application of manure from infected herds close to or directly on pastures without an adequate resting period is, therefore, thought to be an important S. Dublin transmission route and an efficient pathway for the establishment of the bacteria within a herd [ 35 ]. The probability of establishment was highlighted by Fossler et al, who identified a significant risk of shedding of Salmonella bacteria in cows in dairy herds with previous Salmonella history if their own manure was applied to owned or rented land or if cows ate roughage or grassed fields where manure had been applied to the ground surface without additional ploughing [ 78 ].…”
Section: Resulting Biosecurity Assessment Frameworkmentioning
confidence: 99%
“…This is supported by epidemiological studies conducted in comparable cattle populations in other countries [ 32 , 33 ]. Additionally, whole-genome sequencing analysis has identified the geographical clustering of S. Dublin genetic groups [ 34 , 35 , 36 , 37 , 38 ]. Together, this suggests that indirect spread mechanisms are the drivers for the local spread of S. Dublin between herds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serotyping, the WGS approach opens the opportunity to perform further bioinformatics analysis to study Salmonella strains in detail ( 44 ). Especially the detection of genetic markers for virulence and AMR as well as plasmid characterization and SPI detection are important steps in outbreak analysis.…”
Section: Discussionmentioning
confidence: 99%